EMPLOYEE RESILIENCE AND ORGANIZATIONAL SUPPORT AS PREDICTORS OF WORK ENGAGEMENT IN GENERATION Z EMPLOYEES AT TECHNOLOGY COMPANIES IN JABODETABEK - Helmy Raihan Putra; Ayu Dwi Nindyati; Endro Puspo Wiroko (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2025)
This study aims to investigate the roles of employee resilience and organizational support in the work engagement of Generation Z employees in the Jabodetabek area, particularly in technology companies. Quantitative methods were used with 201 participants, and the sampling technique was non-probability, convenience sampling. This study used the Utrecht Work Engagement Scale, the Survey of Perceived Organizational Support, and the Resilience at Work Scale as instruments. The collected data were analyzed using multiple regression analysis. The results showed that employee resilience and organizational support are essential in increasing work engagement among Generation Z employees at technology companies in Jabodetabek. The findings of this research provide valuable insights into the dynamics of work engagement among Generation Z employees at the technology companies in Jabodetabek. Notably, the results indicate that both employee resilience and organizational support play pivotal roles in enhancing work engagement among this specific demographic group in technology companies in the region. These findings contribute to our understanding of the factors that drive employee engagement and may have practical implications for HR and organizational strategies aimed at enhancing the work engagement of Generation Z employees.